Fermentation and Extraction of Antibacterial Metabolite Using Streptomyces spp. Isolated from Taplejung, Nepal - Sah, Shiv Nandan; Majhi, Ramesh; Regmi, Sunil; Ghimire, Arjun; Biswas, Bhageshwor; Yadav, Lalu Prasad; Sah, Ranjit Kumar; Shah, Pradeep Kumar (Journal of Institute of Science and Technology, 2021)
Realizing an increasing need for a novel antibiotic, this study was carried out to screen antibacterial metabolites producing actinomycetes from 15 soil samples collected from Taplejung. Antibacterial metabolites producing actinomycetes were confirmed by primary screening and secondary screening. Macroscopic, microscopic, and biochemical characteristics were used for presumptive identification of probable actinomycetes genera. The potential isolate was cultured in starch casein broth for production of possible antibacterial compound. The antibacterial compound was extracted from fermented broth using organic solvents like ethyl acetate, n-butanol, chloroform, dichloromethane, and methanol. Among 24 isolates, only one (T18) showed antibacterial activity against both Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli, Salmonella Typhi and Pseudomonas aeruginosa) test-bacteria. The isolate was considered as Streptomyces spp based on microscopy and various biochemical, and physiological characteristics. Extracted antibacterial metabolite showed antibacterial activity with a MIC value of 1.2 mg/mL against E. coli (ATCC 25922). The chromatogram in Thin Layer Chromatography showed only one spot exhibited by extract with Rf value 0.87 suggested that the isolate produced a compound that was completely different from the spot with Rf value 0.94 produced by gentamicin (standard). This study revealed the distribution of the potent antibacterial metabolite producing actinomycetes in the soils of Taplejung.